Pengaruh Pengembangan UMKM Dan Tingkat Pengangguran Terhadap Kualitas Hidup Masyarakat - Alma Pakiun; Raflin Hinelo; Sudirman Sudirman; Hais Dama; Ardianyah Ardiansyah (Journal of Economic and Business Education, 2023)
This study uses a quantitative approach. Data collection methods are observation, interviews, and questionnaires. The population in this study are all people who own MSMEs, and unemployed people amounted to 524, while the samples include 50 people. The results of this study indicate that the development of MSMEs and the unemployment rate variables have a simultaneous or joint effect on the community’s quality of life in Oluhuta Village. From the statistical results of simultaneous testing (F tes) of the MSMEs development and the unemployment rate variables on the community’s quality of life. It obtains the Fcount value is greater than Ftable, which is 30,928 2,80 with a significance value of less than 0.000 (0,000 0,05). Thus, hypothesis which states that there is effect of MSMEs development and the unemployment rate simultaneously on the community’s qualityof life can be accepted.